Hands-On Computer Vision with Julia : Build complex applications with advanced Julia packages for image processing, neural networks, and Artificial Intelligence /: Build complex applications with advanced Julia packages for image processing, neural networks, and Artificial Intelligence. (2018) - Cudihins, Dmitrijs
No abstract available